Leaching of Ni–Cu–Fe–S converter matte at varying iron endpoints; mineralogical changes and behaviour of Ir, Rh and Ru - van Schalkwyk, R; Eksteen, Jacques; Akdogan, G. (Elsevier Science BV, 2013)
The Bushveld Igneous Complex in South Africa is a rich source of platinum group elements (PGEs), as well as base metal sulphides. Typical beneficiation routes entail milling and flotation, smelting, matte converting and hydrometallurgical processing of converter matte to selectively recover metal values. The primary focus is on PGE recovery, with the secondary objective of base metals recovery. At the Western Platinum Pty. Ltd. Base Metals Refinery, converter matte typically contains 48% Ni, 29% Cu, 21% S and 0.6–5% Fe by weight, and the major mineral phases have compositions approaching heazlewoodite (Ni3S2), chalcocite (Cu2S) and a Ni–Cu alloy. It has been observed that the iron content of converter matte can have a significant impact on performance of the first stage atmospheric leach, in which the primary goal is to precipitate copper and PGEs from spent electrolyte (via metathesis and cementation reactions) and the secondary goal is the dissolution of nickel.In this work, laboratory scale batch leach tests were carried out with samples of converter matte with varying Fe-endpoints (0.53%, 0.83% and 5.72%), under oxygenated and non-oxygenated conditions, to improve understanding of the effect of the Fe-endpoint. X-ray diffraction and scanning electron microscopy techniques were employed to understand mineralogical changes that take place during leaching. Matte with a higher iron content was characterised by a lower Ni–Cu alloy content than matte with a lower iron content, and the presence of relatively inert pentlandite (NiFe)9S8. Under oxygenated conditions, nickel was leached more readily from low iron matte and copper and PGEs were precipitated more readily onto low iron matte than high iron matte. Under non-oxygenated conditions, copper was precipitated more readily onto the low iron matte and more nickel was leached from a low-iron matte than high iron matte, this can probably be attributed to the presence of the alloy phase in the low iron matte, which galvanically inhibits the metathesis reaction.